Extraction of highly crystalline and thermally stable cellulose nanofiber from Heliconia psittacorum L.f. leaves - Paul, Sharon; Joseph, Anto; Hridhya, P. D.; Badawi, Michael; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Asrofi, Mochamad; Dominic, C. D. Midhun (International Journal of Biological Macromolecules, 2025)
Extracting cellulose nanofibers (CNF) from agro-waste is one of the promising and practical ways to develop sustainable nanocomposites. In this study, cellulose nanofibers were extracted from the leaves of Heliconia psittacorum for the first time. The combination of oxalic acid hydrolysis (5 wt%) and steam explosion was used for the isolation of CNF from the leaves of Heliconia psittacorum. The structural and chemical features of the prepared CNF were analyzed using various techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Solid state 13C Nuclear Magnetic Resonance Spectroscopy (13C NMR), Scanning Electron Microscopy (SEM), Energy Dispersive X ray analysis (EDX), Transmission electron Microscopy (TEM), X-Ray Diffraction (XRD) and Thermogravimetric analysis (TGA). TEM micrographs reported 15 to 40 nm diameter for the nanofibers synthesized. XRD analysis reported 91 % crystallinity index for CNF, whereas that of the untreated sample was 76 %. The maximum degradation of the CNF is reported at 355 degrees C, exceeds the untreated sample (316 degrees C). The tensile strength of the CNF derived paper was found to be 23 MPa. The recovered nanocellulose can be further utilized for various applications such as the automobile industry for developing lightweight parts, biosensors, super capacitors, absorption of greenhouse gases, wastewater treatment, and packaging applications.
Keywords: biomass valorization; Nanocellulose; Waste to resource